2008
DOI: 10.1634/stemcells.2008-0329
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Derived Mesenchymal Stromal Cells Express Cardiac-Specific Markers, Retain the Stromal Phenotype, and Do Not Become Functional Cardiomyocytes In Vitro

Abstract: Although cell fusion between rCMs and MSCs was detectable, the very low frequency (0.7%) could not account for the phenotype of the GFP ؉ MSCs. In conclusion, we have identified an MSC population displaying plasticity toward the cardiomyocyte lineage while retaining mesenchymal stromal cell properties, including a nonexcitable electrophysiological phenotype. The demonstration of an MSC population coexpressing cardiac and stromal cell markers may explain conflicting results in the literature and indicates the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
133
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(145 citation statements)
references
References 56 publications
12
133
0
Order By: Relevance
“…Consistent with recent findings [24,29], cells of the stem cell line used in this study were found to express mesenchymal stem cell markers, CD44, Stro-1, and vimentin ( Fig. 1B-1D; [30,31]) and to possess the capacity to differentiate into mesodermal cell types (Fig. 1E, 1F).…”
Section: Transplanted Adult Human Olfactory Stem Cells Are Mesenchymasupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with recent findings [24,29], cells of the stem cell line used in this study were found to express mesenchymal stem cell markers, CD44, Stro-1, and vimentin ( Fig. 1B-1D; [30,31]) and to possess the capacity to differentiate into mesodermal cell types (Fig. 1E, 1F).…”
Section: Transplanted Adult Human Olfactory Stem Cells Are Mesenchymasupporting
confidence: 91%
“…Our in vitro characterization of the olfactory stem cells used in this study suggests that these cells are mesenchymal stem cells. The cells are immunopositive for the mesenchymal stem cell markers CD44, Stro-1, and vimentin [30,31] and are capable of differentiation into mesenchymal cell types (adipocytes and osteocytes). As Stro-1 is expressed exclusively in the lamina propria of the human olfactory mucosa [36], these cells appear to be similar to previously described populations of olfactory lamina propria-derived mesenchymal stem cells [24].…”
Section: Discussionmentioning
confidence: 99%
“…The ultrastructural maturation in differentiated cardiomyocytes seemed more heterogeneous, and did not reach the fully mature adult phenotype during the observation period. Recently published data reported that murine MSCs inspite of expressing cardiac-specific markers do not become functional cardiomyocytes in vitro (Rose et al 2008). Our result also suggests that human bone marrow-derived MSCs follow a similar pattern in vitro and differentiate into cardiomyocytes with limited functional ability.…”
Section: Resultssupporting
confidence: 74%
“…A recent study by Rose et al has shown that although bone marrow-derived MSCs can be induced to adopt a cardiac muscle phenotype, by expressing cardiac-specific makers, they still retain the MSC phenotype and fail to become functional cardiomyocytes in vitro [63]. The same may be the case here since PAX3-transduced hMSCs still maintain a MSC phenotype (Fig.…”
Section: Discussionsupporting
confidence: 55%